Light Rail Transit (LRT) survey implementation in one of the university in northern Malaysia - Zakaria, Muhammad Afiq; Anuar, Herman Shah (2017)
The research aims to study the use of transportation Light Rail Transit (LRT) at University Utara Malaysia College.Light Rail Transit (LRT) is an electric-powered trains and moving on two tracks to offer a comfortable choice to move in a designated area.This research used quantitative case study method in which questionnaire was used for data collection.A total of 152 undergraduate students were selected using simple random sampling method.The study was conducted to making a screening to the student’s knowledge about Light Rail Transit in terms of time saving, cost, and environmental knowledge. The finding shows that the percentage of agreed students is quiet higher.It proves that Light Rail Transit (LRT) is an efficient transport system to use for the University Utara Malaysia (UUM) students.